Integrated Planning and Regional Development: Lessons Learned from the American "Tri-Cities" Experience in Georgia (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Engineering Sciences Series, 2025)
The unique convergence of urban, suburban, and rural landscapes in the Tri-Cities of Georgia, USA, presents both opportunities and challenges for integrated planning. The studied area has experienced significant growth and transformation, requiring a comprehensive approach to managing land use, infrastructure, and resources amidst ongoing challenges such as uneven development, transportation inefficiencies, and environmental inattention. These challenges highlight the need for strategic regional planning that aligns local priorities with broader regional goals. This research aims to extract lessons learned and understand integrated planning and its impact on regional and national planning, by examining plans and strategies in the Tri-Cities, identifying problems, difficulties, and opportunities for improvement, and observing specific development areas such as infrastructure, housing, and regional legislation. The analysis and induction demonstrate the integration of the Tri-Cities’ development plans that seek to ensure that cities grow in a way that benefits the region as a whole, rather than focusing on individual cities in order to support sustainable growth and regional cooperation. This experience provides locally applicable lessons for promoting sustainable development, addressing the challenges of resource shortages, and balancing economic growth and the environment.
Keywords: Integrated Planning; Integrated Territorial Investment; Regional Cooperation; Tri-cities; Sustainable Development